2005
DOI: 10.1152/ajpheart.01271.2004
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenosides block HIV protease inhibitor ritonavir-induced vascular dysfunction of porcine coronary arteries

Abstract: Ginsenosides have been shown to have potential benefits on the cardiovascular system through diverse mechanisms, including antioxidative property. The objective of this study was to determine whether ginsenosides could prevent coronary arteries from RTVinduced dysfunction. Porcine coronary artery rings were incubated with RTV and ginsenosides Rb1, Rc, and Re for 24 h. Vasomotor function was recorded by a myograph tension system. In response to the thromboxane A2 analog U-46619, the contraction of the vessel ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
44
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 36 publications
5
44
0
1
Order By: Relevance
“…Similar to that, reduced levels of 3-nitrotyrosine was normalized by a-tocopherol only when ritonavir, and not the bona fide proteasome inhibitor ALLN was used. These results are in line with those obtained when ritonavir was used together with ginsenosides or curcumin, a combination that was able to normalize ritonavir-induced vascular dysfunction, most likely by normalization of eNOS and nitric oxide levels in porcine coronary arteries (29,47).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to that, reduced levels of 3-nitrotyrosine was normalized by a-tocopherol only when ritonavir, and not the bona fide proteasome inhibitor ALLN was used. These results are in line with those obtained when ritonavir was used together with ginsenosides or curcumin, a combination that was able to normalize ritonavir-induced vascular dysfunction, most likely by normalization of eNOS and nitric oxide levels in porcine coronary arteries (29,47).…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have shown that ritonavir decreases the expression of eNOS, with consequent decreased levels of NO (28,29), and that the inhibition of proteasome leads to activation of PP2A with consequent de-phosphorylation and reduced eNOS activity (30); thus, despite increased levels of oxidative stress, less 3-nitrotyrosine-modified proteins should be formed after the inhibition of the proteasome by ritonavir treatment. THP-1 monocytes were incubated for 24 h with increasing concentrations of ritonavir or ALLN, with or without cotreatment with a-tocopherol (50 mM) or ethanol solvent control (0.1%).…”
Section: Reduced 3-nitrotyrosine After Proteasome Inhibition By Ritonmentioning
confidence: 99%
“…Many studies have shown that Rg 1 can cause endothelial-dependent relaxation in the rat aorta 11) and enhance endogenous NO production in human umbilical vein endothelial cells, 12) rat kidney, 13) and in porcine coronary arteries. 14) Although some protopanaxadial saponins including ginsenoside Rb 1 have been shown to promote NO release in some tissues, 9) there seem some differences in NO-releasing effect between the protopanaxatriol and protopanaxadiol groups; for example, in rat aorta the protopanaxatriol saponins Rg 1 and Re but not the protopanaxadiol saponins Rb 1 and Rc enhance the release of NO from endothelial cells. 11) In our previous studies on the relationship between the NO-releasing and anti-cardiac hypertrophic effects of ginsenosides, we found that N G -nitro-Larginine-methyl ester (L-NAME), a NOS inhibitor, had no influence on the anti-hypertrophic effect of Rb 1 , 15) suggesting a limited role of NO in the effect of Rb 1 .…”
mentioning
confidence: 99%
“…Total antioxidant status has been reduced in HIV-1 infected patients, probably due depletion of antioxidant molecules when they are consumed in the process of protecting cells against ROS induced oxidative damage in a magnitude that is related to advancement of the disease to AIDS (Ogunro et al, 2005). Endothelial dysfunction induced by HIV-1 PIs may possible be reversed by antioxidants, including ginsenosides, selenium, curcumin (Chai et al, 2005a;Chai et al, 2005b), and resveratrol (Touzet & Philips, 2010). Therefore, it has been proposed by some researches that the oxidative stress and antioxidant status of HIV-1 seropositive patients could be monitored periodically during the disease progression.…”
Section: Antioxidant Status In Hiv-1 Infectionmentioning
confidence: 99%